Green sonochemical synthesis of BaDy2NiO5/Dy2O3 and BaDy2NiO5/NiO nanocomposites in the presence of core almond as a capping agent and their application as photocatalysts for the removal of organic dyes in water - Seyede Raheleh Yousefi; Sobhani, Azam; Hassan Abbas Alshamsi; Salavati-Niasari, Masoud (RSC advances, 2021)
The present work reports the sonochemical synthesis of DBNO NC (dysprosium nickelate nanocomposite) using metal nitrates and core almond as a capping agent. In addition, the effects of the power of ultrasound irradiation were investigated. The BaDy2NiO5/Dy2O3 and BaDy2NiO5/NiO nanocomposites were synthesized with sonication powers of 50 and 30 W, respectively. The agglomerated nanoparticles were obtained using different sonication powers, including 15, 30, and 50 W. The results showed that upon increasing the sonication power, the particle size decreased. After characterization, the optical, electrical, magnetic, and photocatalytic properties of the NC were studied. The nanocomposites showed an antiferromagnetic behavior. In this study, the photocatalytic degradations of two dyes, AR14 and AB92, were investigated in the presence of DBNO NC. Furthermore, the effects of the amount of photocatalyst, the concentration of the dye solution, the type of organic dye, and light irradiation on the photocatalytic activity of the nanocomposite were studied. The results showed that with an increasing amount of catalyst and decreasing concentration of dye, the photocatalytic activity of the nanocomposite was increased. This activity for the degradation of AR14 is higher than that of AB92. Both AR14 and AB92 dyes show higher photocatalytic degradation under UV irradiation than under Vis irradiation.